Written Language Errors Of Dysgraphic Children Aged 9-12 Years In Inclusive Classrooms - Sri Suci Wahyuni; Iskandarsyah Siregar; Kurnia Rachmawati; Nurul Huda Hamzah (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
Dysgraphia is a writing disorder that is often found in children in elementary school. Dysgraphia children are usually called children with special needs or stupid because they are slow in conveying their thoughts through writing. The attitude towards dysgraphia children by teachers and parents is still very lacking and often considered trivial. Therefore, parents and teachers must act actively in learning children's written language. The purpose of this study is to analyze the form and characteristics of written language errors of dysgraphia children aged 9-12 years in the Inclusion Class and to find out the appropriate method for learning written language for dysgraphia children in the Inclusion Class. This research used the qualitative method. The results showed that written language errors in each child were different in terms of the shape of the letters, the thickness of the writing, and the error patterns experienced by each child. The error that is often found in child 1 is the replacement of reflected letters. Child 2 is writing letters upside down. Child 3 is the replacement of consonants. And child 4 is the addition of letters. To help children with dysgraphia learn, various methods of learning are needed, which need to be practiced continuously.